THERMODYNAMIC ANALYSIS OF ENERGY IMBALANCE IN CANCER CELLS - Odilova Nozanin; Qobilova Shahruza; Olimova Ozoda; Shavkat Xolmedov (Modern American Journals, 2025)
Cells maintain their structure and function through continuous energy exchange with their surroundings. These processes are governed by the fundamental laws of thermodynamics , which ensure that energy is conserved while entropy tends to increase. In cancer cells , these principles become especially important , as changes in metabolism support uncontrolled proliferation and disrupt energy balance (Haynie , 2014). ATP plays a central role in this system , providing free energy for endergonic reactions through coupling mechanisms. However , in malignant cells , ATP production and consumption pathways are reprogrammed — a phenomenon known as the Warburg effect. This shift results in altered Gibbs free energy (ΔG) , increased heat production , and changes in cellular heat capacity , all reflecting the thermodynamic imbalance within the cell. Understanding these processes through thermodynamic analysis allows us to connect molecular energy transformations to large-scale biological behavior , revealing how cancer cells sustain their growth far from equilibrium conditions.
Keywords: Bioenergetics, thermodynamics, entropy, Gibbs free energy, cancer metabolism.